Host miRNA-21 promotes liver dysfunction by targeting small intestinal Lactobacillus in mice. Issue 1 (9th November 2020) - Santos, André A.; Afonso, Marta B.; Ramiro, Ricardo S.; Pires, David; Pimentel, Madalena; Castro, Rui E.; Rodrigues, Cecília M.P.
ABSTRACT: New evidence shows that host-microbiota crosstalk can be modulated via endogenous miRNAs. We have previously reported that miR-21 ablation protects against liver injury in cholestasis. In this study, we investigated the role of miR-21 in modulating the gut microbiota during cholestasis and its effects in liver dysfunction. Mice lacking miR-21 had reduced liver damage and were protected against small intestinal injury as well as from gut microbiota dysbiosis when subjected to bile duct ligation surgery. The unique microbiota profile of miR-21KO mice was characterized by an increase in Lactobacillus, a key microbiome genus for gut homeostasis. Interestingly, in vitro incubation of synthetic miR-21 directly reduced Lactobacillus load. Moreover, supplementation with Lactobacillus reuteri revealed reduced liver fibrosis in acute bile duct-ligated mice, mimicking the protective effects in miR-21 knockout mice. D-lactate, a main product of Lactobacillus, regulates gut homeostasis that may link with reduced liver fibrosis. Altogether, our results demonstrate that miR-21 promotes liver dysfunction through direct modulation of the gut microbiota and highlight the potential therapeutic effects of Lactobacillus supplementation in gut and liver homeostasis.